Dampak Warna dan Tipografi terhadap Kenyamanan Pengguna dalam Desain Antarmuka Digital - Rani Chantika; Pebi Mina Husania; Tengku Syahvina Rival Dini; Silfia Rahmadani Sitorus; Puji Sri Alhirani; M. Khalil Gibran (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
Digital interface design plays a vital role in user interaction with software, especially through visual elements such as color and typography. This study was motivated by the need to understand how these visual elements affect user comfort while interacting with an application or website. The purpose of this study was to analyze user perceptions of the use of color and typography, and their impact on visual comfort. The method used was a descriptive quantitative approach by distributing online questionnaires to 20 respondents from various age groups. The collected data were analyzed descriptively by comparing preferences and comfort based on the age of the respondents. The results showed that the majority of respondents felt that color and typography greatly influenced the comfort of using digital interfaces. Dark background colors and sans-serif fonts with proportional sizes proved to be the most preferred choices because they provided reading comfort and reduced eye fatigue. A balanced combination of color and typography was also considered important to improve readability and the overall user experience. In conclusion, the selection and use of appropriate visual elements contribute greatly to creating a friendly and comfortable interface design for users of various age ranges.